3 - Private Provision, National Regulatory Systems and Quality Assurance: A Case Study of Transnational Providers in South Africa - Singh, Mala; Lange, Lis; Naidoo, Prem (Journal of Higher Education in Africa, 2007)
This paper looks into the emergence of transnational provision in South Africa in the context of the expansion of private higher education since the mid-1990s, and of the development of a national policy and regulatory framework that defines the role of higher education in the construction of a democratic society. The article analyses the characteristics of private and transnational provision of higher edu- cation and their impact in South Africa. It concludes with a reflection on the issues which developing countries may (need to) consider when constructing regu- latory frameworks for transnational provision.